2018
DOI: 10.25077/jpi.20.3.151-159.2018
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Mempengaruhi Pendapatan Usaha Ternak Sapi potong di Kecamatan Sitiung, Kabupaten Dharmasraya

Abstract: Keberhasilan usaha ternak sapi potong bergantung pada tiga unsur yaitu bibit, pakan, dan manajemen atau pengelolaan. Tujuan Penelitian adalah untuk menghitung pendapatan usaha ternak sapi potong dan menentukan faktor-faktor yang mempengaruhi pendapatan usaha ternak sapi potong di Kecamatan Sitiung Kabupaten Dharmasraya. Jumlah sampel yang digunakan dalam penelitian ini adalah 43 orang peternak sapi potong. Variabel yang diukur adalah pendapataan usaha ternak sapi potong dan faktor-faktor yang mempengaruhi pend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 0 publications
0
10
0
8
Order By: Relevance
“…Also, the increasing number of livestock ownership will automatically increase the income of the farmers themselves. Following the results of research from [19] reported that the variables that have a significant effect on beef cattle business income are the variables of beef cattle business costs, the number of livestock raised, and the cattle raising system. Meanwhile, the variable farming experience and length of farmers education did not have a significant effect.…”
Section: The Effect Of Individual Farmer Characteristics (X) On Farmers Income Level (Y)mentioning
confidence: 99%
“…Also, the increasing number of livestock ownership will automatically increase the income of the farmers themselves. Following the results of research from [19] reported that the variables that have a significant effect on beef cattle business income are the variables of beef cattle business costs, the number of livestock raised, and the cattle raising system. Meanwhile, the variable farming experience and length of farmers education did not have a significant effect.…”
Section: The Effect Of Individual Farmer Characteristics (X) On Farmers Income Level (Y)mentioning
confidence: 99%
“…Curahan waktu kerja tergantung pada jenis pekerjaan yang dilakukan (Fyka et al, 2019). Tedapat kegiatan yang memerlukan curahan waktu yang banyak, tetapi sebaliknya ada pula jenis-kegiatan yang memerlukan curahan waktu kerja terbatas (Indrayani & Andri, 2018).…”
Section: Pendahuluanunclassified
“…The average number of cows bred by cattlemen was two cows. The revenue depends on the number of cows bred the end of the year, including calves, heifers, and cows (Indrayani & Andri, 2018).…”
Section: Analysis Of Sahiwal Cross Cattle Business Revenuementioning
confidence: 99%